Evaluation of quality of service in Early Intervention: A systematic review - Inmaculada Concepción Jemes Campaña; Rita Pilar Romero-Galisteo; María Teresa Labajos Manzanares; Noelia Moreno Morales (Elsevier, 2019)
Introduction: Early Intervention (EI), as a paediatric service, has the duty of quantifying the results and the quality of its services provided. The accessibility of valid and reliable tools allows professionals to evaluate the quality of these services. Main objective: The aim of this study is to review the scientific literature on tools used to measure the methodological and service quality in EI. Methods: A search was made in different databases: Medline (from PubMed), Web of Science, PsycINFO, Cochrane, Scopus, ERIC and Scielo. The methodological quality of the studies was tested using the COSMIN scale. Results: A total of 13 manuscripts met the criteria to be included in this review. Ten of them received a "good" or "reasonable" score based on the COSMIN scale. Conclusions: Despite its importance, there is no consensus among authors on the measurement of service quality in EI. It is often the family of the children attended in EI that are considered the target to study, although the opinion of professionals carries more weight and completes the information. Resumen: Introducción: La Atención Temprana (AT), como servicio pediátrico, obliga a cuantificar resultados de intervención y calidad de servicio ofrecido. La disposición de instrumentos de medida válidos y fiables permitirá a los profesionales evaluar la calidad de estos servicios. Objetivo principal: Revisar la literatura científica, analizar la calidad metodológica de las herramientas utilizadas en AT para la medición de la calidad de servicio. Métodos: Se realizó una búsqueda en diferentes bases de datos: Medline (a través de Pubmed), Web of Science, PsycINFO, Cochrane, Scopus, ERIC y Scielo. La calidad metodológica de los estudios identificados se evaluó a través de la escala Consensus-based Standards for the Selection of Health Measurement (COSMIN). Resultados: Se seleccionaron 13 artículos que cumplieron los criterios de inclusión, de los cuales 10 obtuvieron una puntuación «buena» o «razonable» según la escala COSMIN. Conclusiones: Pese a su importancia, aún no existe consenso entre los autores sobre la medición de la calidad de servicio en AT. Habitualmente, es la familia de los niños atendidos en AT la población sobre la que se realizan los estudios, aunque la perspectiva de los profesionales toma auge y completa la información.